FACTORS TO STRENGTHEN THE IDEOLOGICAL IMMUNITY OF YOUNG PEOPLE IN THE PROCESS OF IDEOLOGICAL EDUCATION - Abdurazokov Gulmurod (Western European Studies, 2024)
This article analyzes the essence of the concept of «ideological factors» from a philosophical point of view. Today, the main directions of moral measures that should be implemented to protect the young generation from various ideological threats have been highlighted.
Keywords: youth; ideology; thought